ETOS KERJA ISLAM - Dalinur M. Nur (Wardah, 2013)
Work ethic problem has become one of the talk is lively in our society. The talks are not uncommon in the atmosphere of fear that if we as a nation can not grow a good work ethic then our nation will likely remain behind by other nations, including by neighboring nations in Southeast Asia or the environment, even more so , East Asia.In the Islamic view, work is something that is important, even work is a must (obligation). Is not the duties of man as the vicegerent of Allah on earth as the manager for the prosperity of the earth's natural resources. Humans are obliged to carry out the task, not just maintain it. Because human failure would lead to his duties and rank crushed down to the lowest place